Digital Marketing Capability and Firm Performance in B2B Industrial Ecosystems: The Parallel Mediation of Market Agility and Customer Relationship Quality - Nuraeni; Agustini Tanjung; Sri Wahyuningsih; Riana Oktaviani (Fundamental and Applied Management Journal, 2026)
Global industrial ecosystems are undergoing digital transformation, yet business-to-business (B2B) firms often report that technological investments do not consistently improve financial or operational performance, a phenomenon termed the "digitalization paradox." Grounded in Dynamic Capability Theory (DCT), this study investigates the mediation roles of market agility and customer relationship quality in the relationship between digital marketing capability and firm performance. A quantitative explanatory design was employed, with empirical data collected from 165 managerial respondents in the Jababeka Industrial Estate, Indonesia. The model was evaluated using Partial Least Squares Structural Equation Modeling (PLS-SEM). The structural analysis indicates full parallel mediation. The direct impact of digital marketing capability on firm performance is non-significant (beta = 0.067, p = 0.304). Digital marketing capability shows significant positive associations with both market agility (beta = 0.503, p < 0.001) and customer relationship quality (beta = 0.551, p < 0.001). The indirect effect through customer relationship quality (beta = 0.286) is larger than the indirect effect through market agility (beta = 0.155). The results suggest that in the B2B industrial context, digital marketing capability acts as an antecedent to higher-order capabilities rather than a direct driver of firm performance. Limitations include a cross-sectional design, a single-key-informant approach, and a single-site context, which suggest that future research should adopt multi-source longitudinal designs to further validate these associations.